2019
DOI: 10.3390/ijms20010214
|View full text |Cite
|
Sign up to set email alerts
|

Recipient ADAMTS13 Single-Nucleotide Polymorphism Predicts Relapse after Unrelated Bone Marrow Transplantation for Hematologic Malignancy

Abstract: Relapse remains a major obstacle to the survival of patients with hematologic malignancies after allogeneic hematopoietic stem cell transplantation. A disintegrin-like and metalloprotease with a thrombospondin type 1 motif (ADMATS13), which cleaves von Willebrand factor multimers into less active fragments, is encoded by the ADAMTS13 gene and has a functional single-nucleotide polymorphism (SNP) rs2285489 (C > T). We retrospectively examined whether ADAMTS13 rs2285489 affected the transplant outcomes in a coho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
(36 reference statements)
0
5
0
Order By: Relevance
“…Lasparaginase is known to alter many coagulation and anticoagulant proteins, whereas ALL patients are often treated with L-asparaginase in chemotherapy [18,19], and L-asparaginase may be a potential cause of ADAMTS-13 activity, which is worth researching in detail in the future. Lower translational activity associated with the ADAMTS-13 rs2285489 C/C genotype in hepatic stellate cells might contribute to an increased incidence of relapse [20], which suggests that ADAMTS-13 Fig. 2 The survival curve started from the day of onset, followed for 24 months since the day the leukemia was onset.…”
Section: Discussionmentioning
confidence: 99%
“…Lasparaginase is known to alter many coagulation and anticoagulant proteins, whereas ALL patients are often treated with L-asparaginase in chemotherapy [18,19], and L-asparaginase may be a potential cause of ADAMTS-13 activity, which is worth researching in detail in the future. Lower translational activity associated with the ADAMTS-13 rs2285489 C/C genotype in hepatic stellate cells might contribute to an increased incidence of relapse [20], which suggests that ADAMTS-13 Fig. 2 The survival curve started from the day of onset, followed for 24 months since the day the leukemia was onset.…”
Section: Discussionmentioning
confidence: 99%
“…The HO-1 rs2071746 SNP was analyzed in 593 HLA-A, -B, -C, -DRB1, -DQB1, and -DPB1 allele-matched, unrelated BMT donor-transplant recipient pairs (Table 1). Based on the disease status and other risk factors that influence post-transplant outcomes, as previously reported [22,[27][28][29], standard-risk disease was defined as acute myeloid leukemia (AML), acute lymphoblastic leukemia (ALL), or multiple myeloma (MM) in the first complete remission; malignant lymphoma (ML) in any complete remission; or myelodysplastic syndrome (MDS) or chronic myeloid leukemia (CML) in the chronic phase. Both ALL and AML, which were in the second complete remission, were included in the high-risk group, according to recent reports [27,29] indicating that patients with AML and ALL in the second complete remission have worse post-transplant outcomes than those in the first complete remission.…”
Section: The Frequencies Of Ho-1 Genotypesmentioning
confidence: 99%
“…One important single nucleotide polymorphism (SNP) in the promoter region of the HO-1 gene, rs2071746 (-413A>T), is functional, and the major A allele is reported to be associated with higher expression of HO-1 than the minor T allele [18,19]. There is growing evidence to support that non-human leukocyte antigen (HLA) genetic polymorphism represents a significant determinant of outcomes after allo-HSCT [20][21][22][23][24][25][26]. These findings prompted us to investigate the impact of the rs2071746 SNP in the HO-1 gene on the clinical outcomes of patients undergoing allogeneic bone marrow transplantation (BMT), using an HLA allele-matched, unrelated donor through the Japan Marrow Donor Program (JMDP).…”
Section: Introductionmentioning
confidence: 99%
“…However, lifethreatening complications associated with allogeneic SCT, such as severe infection, organ damage, and graft-versushost disease (GVHD), remain obstacles to overcome [1]. Recently, increasing evidence has suggested that non-HLA genetic polymorphisms significantly influence outcomes after allogeneic SCT [2][3][4][5][6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%